Green Budgeting Accountability in Yogyakarta: Governance Barriers and Financial Reporting Transparency - Zulfatun Ruscitasari; Novi Diah Wulandari (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The Net Zero Emissions target has accelerated the adoption of green budgeting. However, despite achieving the highest accountability rating (SAKIP AA), the Special Region of Yogyakarta still faces a gap between its policy commitments and the transparency of its financial reporting. Objective: This study aims to analyze the accountability challenges in implementing green budgeting in Yogyakarta. Methods: This qualitative study employed a case study design using semi-structured, in-depth interviews with five key informants (INF-01 to INF-05) from Bapperida, BPKAD, DLHK, and public sector accounting experts. Document analysis was conducted on the RKPD, KUA-PPAS, and Notes to the 2021–2025 Financial Statements (CaLK). Data were analyzed using a six-stage thematic analysis, with validity ensured through data triangulation and member checking. Results: The main barriers to implementation were a lack of specific technical guidelines, sectoral ego, and differing perceptions across agencies regarding environmental activity classification. The rigidity of the national SIPD system, which lacks green tagging features, further complicates the identification of green expenditures. Consequently, green costs are embedded within routine expenditure items in the CaLK, resulting in re-labeling practices to meet administrative requirements. Moreover, limited regional fiscal capacity and shifting policy priorities contribute to a gap between planning and actual implementation. Conclusion: High accountability ratings (SAKIP AA) do not ensure substantive sustainability accountability, as green budgeting in Yogyakarta remains largely symbolic. Strengthening implementation requires integrating the Green Chart of Accounts into SIPD, developing cross-sectoral classification standards, and enhancing transparency in environmental cost disclosure. The findings provide actionable guidance for local governments seeking to align fiscal governance with sustainability commitments.